Knowledge, Attitude, and Practice towards Disaster Preparedness among Medical Personnel in Emergency Departments in Malaysia - Amran, Dora Natasha; Sjamun Sjahid, Afifah; Md Noh, Abu Yazid; Abu Bakar, Mimi Azliha; Yaacob, Normalinda; Ismail, Ahmad Filza (IIUM Medical Journal Malaysia, 2025)
INTRODUCTION: Disasters are incidents that can cause damage to properties and loss of lives. Disaster preparedness is a set of measures undertaken in planning for disaster situations. The objectives of this study were to determine the level of knowledge, attitude, and practice (KAP) towards disaster preparedness and its associated factors among emergency department (ED) medical personnel. MATERIALS AND METHODS: This study was conducted in 12 hospitals in Malaysia. A validated questionnaire was used and 427 participants were involved. This study was carried out from March 2019 to March 2020. RESULTS: This study showed that ED medical personnel in Malaysia had adequate KAP towards disaster preparedness, which scored 91.6%, 78.2%, and 61.1%, respectively. An increased level of knowledge was related to experience and training in disaster response, whereby the increased level of practice was associated with duration of working experience. However, there was no association between the level of attitude and disaster preparedness. CONCLUSION: Continuous education and training on disaster preparedness for ED medical personnel are necessary to prepare staff in the event of disaster and to improve the healthcare system